Efficacy of Recombinant Human Parathyroid Hormone 1–34 and Vitamin K2 Combination Therapy in Postmenopausal Osteoporosis - Zhang, Zhuo; Xia, Kun; Gong, Wentao; Mai, Ruopeng; Liu, Peng; Lu, Zhaogang (Hormone and Metabolic Research, 2024)
This study aimed to assess the efficacy and safety of a combined recombinant human parathyroid hormone 1–34 [rhPTH (1–34)] and vitamin K2 therapy versus vitamin K2 alone in the treatment of postmenopausal osteoporosis. A total of 77 postmenopausal osteoporosis patients were randomly divided into two groups. Patients in one group received vitamin K2 alone, while patients in the other group received a combination of rhPTH (1–34) and vitamin K2. Bone mineral density (BMD), electrolyte levels, pain scores, bone metabolism levels, and adverse drug reactions were compared pre- and post-treatment. Both two treatments improved BMD, blood calcium concentrations, pain scores, and increased osteocalcin and osteoprotegerin levels. Notably, the combined rhPTH (1–34) and vitamin K2 treatment demonstrated superior efficacy in improving BMD and bone metabolism markers. Furthermore, there was no significant difference in the incidence of adverse reactions between the two groups, indicating the safety of the combined treatment. In summary, the combined therapy of rhPTH (1–34) and vitamin K2 exhibited more potent efficacy in the treatment of postmenopausal osteoporosis, more effectively enhancing BMD and bone metabolism markers than vitamin K2 alone, without a significant increase in adverse reactions.
Keywords: postmenopausal osteoporosis; recombinant human parathyroid hormone 1-34; vitamin K2; BMD; bone metabolism